J06 Nutritional management of individuals with Huntington's disease: EHDN standards of care nutritional guidelines. (16th November 2010) - Brotherton, A; Campos, L; Rowell, A; Zoia, V; Simpson, S A
Abstract : Background: Good nutritional care is a fundamental element of the management of individuals with Huntington's disease and all patients with Huntington's disease will, at some time, need dietary intervention because of the sequelae of the disease, yet there are no European nutritional guidelines. Aim: The aim was to develop nutritional guidelines to facilitate optimal nutritional screening, assessment and management of individuals throughout all stages of HD, with the aim of improving the standard of nutritional care delivered and to ensure the nutritional management of individuals with HD is based on sound evidence and current best clinical practice. Methods: Literature was systematically searched in an attempt to ensure that the recommendations are based on sound evidence. Where evidence is lacking, specific guidance is based on consensus expert dietetic opinion of the European Huntington's Disease Network Standards of Care (SoC) Dietitians group which brought together expert Dietitians from across Europe. Outcome: The SoC guidelines highlight the fundamental nutritional issues for individuals with HD; nutritional screening, assessment and care planning; nutrition and function; nutrition and oral health; the multidisciplinary approach to nutritional treatment; the nutritional challenges resulting from the impact of the behavioural aspects of the disease and the importance of respecting autonomy when delivering nutritional care. Key recommendations within the guidelines include the use of validated nutritional screening fit for purpose, early referrals for a preventative approach to weight management and comprehensive nutritional assessment with appropriate management and timely reviews. Adequate education and training (in communication, feeding techniques, long term tube feeding) for those involved in the nutritional care of individuals with HD is advocated. Conclusions: Nutritional screening together with the delivery of good nutritional care is fundamental to the care of an individual with HD. For clinicians involved in HD management these SoC nutritional guidelines will offer an invaluable insight into the role of the Dietitian and guidance on the nutritional assessment and management of the individual with HD. The provision of nutritional care varies widely between countries. Implementation of these nutritional guidelines across Europe should improve the quality of nutritional care delivered to individuals with Huntington's disease.